The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11666-018-0775-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Corrosion Performance of HVOF-Sprayed Coatings Produced Using Conventional and Suspension WC-Co Feedstock

Abstract: Corrosion properties of nanostructured coatings deposited by suspension high-velocity oxy-fuel (S-HVOF) via an aqueous suspension of milled WC-Co powder were compared with conventional HVOF-sprayed coatings. Microstructural evaluations of these coatings included x-ray diffraction and scanning electron microscopy equipped with an energy-dispersive x-ray spectroscopy. The corrosion performance of AISI440C stainless steel substrate and the coatings was evaluated in a 3.5 wt.% NaCl aqueous solution at * 25°C. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 39 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…The carbide coating micrographs are presented in Figure 4c,d for WC-12Co and WC-10Co4, respectively. Both coatings had porosity under 1% and hardness above 1200 HV 0.3 , as shown in Table 3, which is consonant with values published by other authors [45,46]. The morphology is composed of particles of WC, which is the lighter phase uniformly distributed in Figure 4c,d, and the metal matrix or binder, the darker phase in Figure 4c,d.…”
Section: Characterization Of Coatingssupporting
confidence: 89%
“…The carbide coating micrographs are presented in Figure 4c,d for WC-12Co and WC-10Co4, respectively. Both coatings had porosity under 1% and hardness above 1200 HV 0.3 , as shown in Table 3, which is consonant with values published by other authors [45,46]. The morphology is composed of particles of WC, which is the lighter phase uniformly distributed in Figure 4c,d, and the metal matrix or binder, the darker phase in Figure 4c,d.…”
Section: Characterization Of Coatingssupporting
confidence: 89%
“…Myalska et al [4] showed that the introduction of TiC nanoparticles into a conventional WC-17Co powder slows down the WC carbide decomposition process and improves tribological properties. Attempts are also being made to produce carbide coatings in the process of high velocity spraying from suspensions [5]. A lower resistance of WC-Co coatings sprayed from suspensions was found in comparison to coatings sprayed conventionally with the HVOF method.…”
Section: Introductionmentioning
confidence: 99%
“…Under this condition, the impedance can be determined via Equation (2) [ 35 ]: where is the angular frequency, and and Q are parameters that are independent of the frequency. When , Q corresponds to an ideal capacitor; otherwise, Q characterizes the non-uniform charge distribution along the electrode/solution interface due to surface heterogeneities [ 36 ].…”
Section: Resultsmentioning
confidence: 99%